Chronic difficulties are associated with poorer psychosocial functioning in the first year post‐diagnosis in epithelial ovarian cancer patients. Issue 6 (1st April 2021) - Garvin, Lauren; Slavich, George M.; Schrepf, Andrew; Davis, Lauren Z.; Thaker, Premal H.; Goodheart, Michael J.; Cole, Steve W.; Sood, Anil K.; Lutgendorf, Susan K.
Abstract: Objective: Ovarian cancer is characterized by poor prognosis, high levels of distress, disturbed sleep, and compromised quality of life (QOL). Although life stressors have been shown to significantly impact physical and psychological health in cancer populations, no studies have used a high‐resolution stress assessment to differentiate effects of acute versus chronic stressors among women with ovarian cancer. We addressed this issue in the present prospective longitudinal study by examining how acute and chronic stress exposure in the year pre‐diagnosis relate to depressive symptoms, sleep quality, and QOL over the first year post‐diagnosis in women with ovarian cancer. Methods: One hundred thirty‐seven women completed the Life Events and Difficulties Schedule within a month of initial treatment for suspected ovarian cancer. Depressive symptoms, sleep, and QOL were measured pre‐treatment, at six months, and one‐year post‐diagnosis. Mixed models were used to examine associations of acute and chronic stress pre‐diagnosis with (a) change in psychosocial outcomes over the first year post‐diagnosis and (b) levels of psychosocial outcomes across all time points. Results: Both the number and severity of chronic difficulties (but not acute life events) were related to significantly greater depression, and poorer sleep quality and QOL, across all time‐points. In contrast, these stress indices were unrelated to changes in psychosocial functioning over time. Conclusions: Chronic but not acute stress exposure predicted average levels of depression, sleep, and QOL in the first year post‐diagnosis among women with ovarian cancer. Assessing stressors and designing interventions for reducing stress may thus be beneficial for ovarian cancer patients.